Traditional Chinese Humor - Wells, Henry W. (Indiana University Press, 1971)
A beguiling world informed by a distinctive sense of the comic is opened to Western readers in this perceptive book. Beginning with the arts of painting and sculpture, the author proceeds to demonstrate the vital role of humor in the work of Chinese poets and other writers, many of whom cultivated the art of smiling at life's incongruities. Copious quotations in English translation make the charm of Chinese humor accessible to all.